2019
DOI: 10.1002/bab.1737
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of novel DNA aptamer against colorectal carcinoma Caco‐2 cells

Abstract: Aptamers are short, single-stranded nucleic acid (DNA or RNA) oligonucleotides that can be obtained by a technique called systematic evolution of ligands by exponential enrichment (SELEX) in vitro. Due to superior properties such as small size, high binding affinity, and stability, they are considered to be feasible tools for diagnosis and treatment of disease. In the current study, we attempted to screen a high-affinity DNA aptamer to selectively target the colorectal carcinoma Caco-2 cells by using cell-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Cell-SELEX is considered to have practical applications particularly in oncology, as this approach can select aptamers specific for the cancer cell targets. Employing Cell-SELEX, aptamer-based probes have been developed for a number of cancers, including cervical cancer [27,28], ovarian cancer [29,30], liver cancer [31], prostate cancer [32], breast cancer [33,34], glioma, [35], colorectal carcinoma [36], and lung carcinoma [37]. A number of cell-SELEX variants have been developed in the last years.…”
Section: Generation Of Aptamersmentioning
confidence: 99%
“…Cell-SELEX is considered to have practical applications particularly in oncology, as this approach can select aptamers specific for the cancer cell targets. Employing Cell-SELEX, aptamer-based probes have been developed for a number of cancers, including cervical cancer [27,28], ovarian cancer [29,30], liver cancer [31], prostate cancer [32], breast cancer [33,34], glioma, [35], colorectal carcinoma [36], and lung carcinoma [37]. A number of cell-SELEX variants have been developed in the last years.…”
Section: Generation Of Aptamersmentioning
confidence: 99%
“…Our results demonstrated that EPC-aptamer had a superior binding efficiency with EPCs compared with HFs and SMCs, which indicated that EPCaptamer was specific to EPCs. Yasen et al 34 tested binding affinity of the DNA aptamer to Caco-2 cells. The result showed that binding ratio was 44.2%, which was lower than our result.…”
Section: Discussionmentioning
confidence: 99%
“…Yasen et al . 34 tested binding affinity of the DNA aptamer to Caco-2 cells. The result showed that binding ratio was 44.2%, which was lower than our result.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible to detect and analyze the tumor cells without known biomarkers. To date, numerous aptamers for diverse cell lines have been generated, such as those against lymphocytic leukemia, myeloid leukemia, glioblastoma, ,, colon cancer, liver cancer, breast cancer, lung cancer, cervical cancer, , and ovarian cancer. , Third, the target molecules specifically bound by aptamers can be identified to discover new biomarkers for disease diagnosis and therapy. The cell surface markers identified by cell-SELEX and aptamer-based targeted proteomics have been summarized in other reviews. , Additionally, many cell-SELEX variants have been developed, including cell-internalization SELEX for selecting aptamers with cellular internalization capability, , 3D cell-SELEX, tissue-SELEX, and even in vivo -SELEX for selecting robust aptamers in mimicked or natural complex physiological environments. , …”
Section: Aptamer Evolution For Circulating Target Detectionmentioning
confidence: 99%